Study of the Effect of Biosynthesized Silver Nanoparticles Using Coriandrum Sativum Leaf Extract on Some Types of Pathogenic Bacteria - Hamood, Ihab Ahmad; Hamad, Shefaa Abas; Nijris, Osama Nadhom (Journal of Neonatal Surgery, 2025)
The capacity to combat common infectious infections has been diminished by the overuse and frequent administration of conventional antibiotics, necessitating numerous medical procedures to prevent this condition. Therefore, one of the biggest threats to the effective treatment of bacterial diseases is the development of new antibacterial systems against drug-resistant microorganisms. Biocompatible nanomaterials provide potential strategies to prevent antimicrobial resistance to drugs, mainly by improving the therapeutic effect of existing antimicrobial drugs. Nanoparticles, also known as nanotechnology, have special physical and chemical characteristics, including a large surface area in relation to size, high reactivity, a functional structure, and a very small size that can be regulated, ranging from 1 to 100 nm. Coriander leaf extract was used to create silver nanoparticles, which were then thoroughly investigated using electrokinetic nanoparticles, atomic force microscopy (AFM), Fourier transform infrared spectroscopy (FT-IR), ultraviolet and visible spectroscopy (UV-Vis), and X-ray scattering (EDX). Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) were used to assess the properties. Different concentrations were prepared for the nanoparticles: 500, 400, 300, 200, and 100 μg/ml. Their inhibitory efficacy was tested against isolates of Gram-positive Staphylococcus aureus and Gram-negative Pseudomonas aeruginosa using the well diffusion method. The outcomes of the silver nanoparticle influence evaluated the efficiency of biosynthetic silver nanoparticles against bacterial isolates at five different concentrations: 500, 400, 300, 200, and 100 μg/ml. Most of the concentrations were successful in preventing the bacterial isolates from growing. The results showed that the effect of silver nanoparticles was better against the Gram-positive Staphylococcus aureus isolates than against the Gram-negative Pseudomonas aeruginosa isolates. The highest inhibitory efficacy was recorded with diameter rates of 22.00 mm for Staphylococcus aureus and 15.00 mm for Pseudomonas aeruginosa. The aqueous extract of coriander leaves has proven its ability to reduce and synthesize silver nanoparticles. When it comes to bacterial isolates, silver nanoparticles have shown the strongest inhibitory activity.